EXPERIMENTAL INVESTIGATION & OPTIMIZATION OF WIRE ELECTRICAL DISCHARGE MACHINING (WEDM) PARAMETERS FOR SURFACE ROUGHNESS & MATERIAL REMOVAL RATE IN MACHINING OF AISI D3 TOOL STEEL - Shailesh Pawar, Onkar Phalake, Pravin Somdale, Omkar Patil, Samarth Mane-Deshmukh (International Journal of Innovations in Engineering Research and Technology, 2022)
This paper presents the outcomes of an experimental analysis carried out to study the effect of micro-sized metal powders, when they are mixed to the dielectric fluid, during Wire Electric Discharge Machining (EDM) of different steels. The work piece material selected as AISI D3 tool steel, peak current, pulse on time, pulse off time, and wire feed rate and mixing of fine metal powders(copper) in dielectric fluid are taken as process input parameters. Material removal rate and Surface Roughness are taken as output parameters to measure the process efficiency. A newly designed experimental set up has been used to perform the task. Taguchi design of experiments is used to conduct experiments. The achieved results of this work indicate that the addition of fine metal powders in dielectric increases the material removal rate and reduces the surface roughness.